18F‐fluoride PET as a noninvasive imaging biomarker for determining treatment efficacy of bone active agents at the hip: A prospective, randomized, controlled clinical study. (21st May 2013) - Frost, Michelle L; Moore, Amelia E; Siddique, Musib; Blake, Glen M; Laurent, Didier; Borah, Babul; Schramm, Ursula; Valentin, Marie‐Anne; Pellas, Theodore C; Marsden, Paul K; Schleyer, Paul J; Fogelman, Ignac
ABSTRACT The functional imaging technique of 18F‐fluoride positron emission tomography (18F‐PET) allows the noninvasive quantitative assessment of regional bone formation at any skeletal site, including the spine and hip. The aim of this study was to determine if 18F‐PET can be used as an early biomarker of treatment efficacy at the hip. Twenty‐seven treatment‐naive postmenopausal women with osteopenia were randomized to receive teriparatide and calcium and vitamin D (TPT group, n = 13) or calcium and vitamin D only (control group, n = 14). Subjects in the TPT group were treated with 20 µg/day teriparatide for 12 weeks. 18F‐PET scans of the proximal femur, pelvis, and lumbar spine were performed at baseline and 12 weeks. The plasma clearance of 18F‐fluoride to bone, Ki, a validated measurement of bone formation, was measured at four regions of the hip, lumbar spine, and pelvis. A significant increase in Ki was observed at all regions of interest (ROIs), including the total hip (+27%, p = 0.002), femoral neck (+25%, p = 0.040), hip trabecular ROI (+21%, p = 0.017), and hip cortical ROI (+51%, p = 0.001) in the TPT group. Significant increases in Ki in response to TPT were also observed at the lumbar spine (+18%, p = 0.001) and pelvis (+42%, p = 0.001). No significant changes in Kiwere observed for the control group. Changes in BMD and bone turnover markers were consistent with previous trials of teriparatide. In conclusion, this is the first study to our knowledge to demonstrate that 18F‐PET can be used as an imaging biomarker for determining treatment efficacy at the hip as early as 12 weeks after initiation of therapy.